2021
DOI: 10.3390/biomedicines9111507
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficacy of Mesenchymal Stem/Stromal-Based Therapy for Treatment of Inflammatory Bowel Diseases

Abstract: Inflammatory bowel diseases (IBD) consisting of persistent and relapsing inflammatory processes of the intestinal mucosa are caused by genetic, environmental, and commensal microbiota factors. Despite recent advances in clinical treatments aiming to decrease inflammation, nearly 30% of patients treated with biologicals experienced drawbacks including loss of response, while others can develop severe side effects. Hence, novel effective treatments are highly needed. Mesenchymal stem/stromal cell (MSCs) therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…As it shares many features with human CD, the 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis animal model has been used to study the mechanism and treatment of human CD. Preclinical animal experiments have confirmed that MSCs could significantly improve clinical abnormalities in TNBS-induced colitis mice and reduce lesion scores and inflammation in the gut [ 13 ]. However, the mechanism by which MSCs alleviate CD is still unclear and it needs further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…As it shares many features with human CD, the 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis animal model has been used to study the mechanism and treatment of human CD. Preclinical animal experiments have confirmed that MSCs could significantly improve clinical abnormalities in TNBS-induced colitis mice and reduce lesion scores and inflammation in the gut [ 13 ]. However, the mechanism by which MSCs alleviate CD is still unclear and it needs further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on numerous studies in experimental immunemediated disorders, better efficacy is achieved when the MSCs were infused during the early phases of the disease (9,33). We therefore infused 3x10 6 MSCs per mouse during the onset of joint inflammation soon after serum administration from K/ BxN arthritic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the low survival rates of stem cells that are injected intravenously into the targeted area to treat intracranial diseases, the injected stem cells may also migrate to other sites and produce side effects. Therefore, some techniques have been developed to promote colonic mucosal healing through interventional radiology and an intra-arterial injection of MSCs into the ileum, and clinical trials have also suggested their safety and efficacy[ 32 ]. In a recent study, a temperature-responsive Petri dish was used to endoscopically transplant MSC sheets into the inflammatory area of mice with TNBS-induced colitis.…”
Section: Use Of Mscs and Their Derivatives In The Treatment Of Ibdmentioning
confidence: 99%
“…Currently, patients with IBD are treated with 5-ASA compounds (mainly mesalamine), glucocorticoids (conventional and other forms, such as budesonide and beclomethasone), antibiotics (usually ciprofloxacin and metronidazole), immunomodulators (mainly AZA/6-MP or methotrexate) and biological agents[ 32 , 46 ]. The aim of these treatments is to inhibit intestinal inflammation and ultimately improve the quality of life of patients with IBD[ 47 ].…”
Section: Enhancement Of the Therapeutic Effects Of Mscs On Ibdmentioning
confidence: 99%
See 1 more Smart Citation